(untitled) (International journal of artificial intelligence, 2024)
The problem of children's traumatism is an extremely urgent medical and social problem in the world's population of all regions. According to reports, more than 186,000 children die each year in the world as a result of road accidents and other impacts. For this reason, it is important to regularly study and analyze the causes of children's traumatism, their details, the consequences and ways to eliminate the symptoms of copulation.